Assessment of Water Use Efficiency in Dairy Production Systems - Letha Devi, G; Mech, Anjumoni; Gorti, Ravikiran; Sejian, Veerasamy (Indian Journal of Extension Education, 2022)
Increasing water scarcity and simultaneously growing demands for food and feed challenge agricultural production. Globally livestock feed sourcing is one of the major causes for water depletion, therefore increasing livestock water use efficiency (LWUE) is necessary. In this direction, primary data was collected from 240 small and medium sized dairy farms in Karnataka, India during the period 2018-2021. Water inputs (by animals) considered were drinking water, water contained in forages, water for on-farm servicing, water for crop irrigation and water for all upstream inputs other than feeds and milk was considered as output. The water inputs through forage and other feed ingredients were more as compared to water inputs through drinking water and that used for on farm servicing operations such as cleaning etc. Average direct consumptive water use by smallholder system was found to be 130 litres per day per animal and 205 litres per day for commercial dairies. Water use efficiency for the smallholder system was 0.85 and for the commercial dairying it was 1.62.